A new Early Cretaceous shore bug (Hemiptera: Heteroptera: Saldidae) from China - Zhang, Weiting; Yao, Yunzhi; Ren, Dong (Zootaxa, 2013)
A new genus Luculentsalda Zhang, Yao & Ren gen. nov. (type-species Luculentsalda maculosa Zhang, Yao & Ren sp. nov.) of Saldidae is described and illustrated. All the specimens were collected from Early Cretaceous Yixian Formation of Huangbanjigou, Beipiao City, Liaoning Province, China. New findings suggest that the subfamily Chiloxanthinae prob-ably originated in the eastern part of Laurasia.